Intervention mapping for the development of a strategy to implement the insurance medicine guidelines for depression - Anema Johannes R; Schellart Antonius JM; Zwerver Feico; Rammeloo Kathelijne C; van der Beek Allard J (BMC, 2011)
Abstract Background This article describes the development of a strategy to implement the insurance medicine guidelines for depression. Use of the guidelines is intended to result in more transparent and uniform assessment of claimants with depressive symptoms. Methods The implementation strategy was developed using the Intervention Mapping (IM) method for alignment with insurance-medical practice. The ASE behavioural explanation model (Attitude, Social Influence and Self-Efficacy) was used as theoretical basis for the development work. A literature study of implementation strategies and interviews with insurance physicians were performed to develop instruments for use with the guideline. These instruments were designed to match the needs and the working circumstances of insurance physicians. Performance indicators to measure the quality of the assessment and the adherence to the guidelines were defined with input from insurance physicians. Results This study resulted in the development of a training course to teach insurance physicians how to apply the guidelines for depression, using the aforementioned instruments. The efficacy of this training course will be evaluated in a Randomized Controlled Trial. Conclusions The use of IM made it possible to develop guideline support instruments tailored to insurance medical practice.